Demobilization in Subsaharan Africa - Kingma, K. author. aut Link
XVIII, 268 p.
Keywords: In the early and mid-1900s, several African countries demobilized part of their armed forces. This book analyzes, in the light of Africa's large development challenges and continuing wars and insecurity, the question of how demobilizations have contributed to peace and human development. It also explores what we can learn from the different approaches that have been taken.